How do you multiply #(3x+1)(x-2)#?

1 Answer
Jul 4, 2015

Answer:

Multiply each term in one factor time each term in the other factor

Explanation:

We need to multiply: #3x# times #x# and times #-2# and we need to multiply #1# times #x# and times #-2#.

We can (but are not required to) write:

#(3x+1)(x-2) = (3x*x) + (3x * -2) + (1*x)+ (1*-2)#

We get:

#(3x+1)(x-2) = 3x^2 + (-6x) + x+ (-2)#

which is also equal to
#(3x+1)(x-2) = 3x^2 -6x + x -2#

Now simplify by combining like terms (#-6x+x = -5x#)

#(3x+1)(x-2) = 3x^2 -5x -2#